Skill proportion in education sector - Said, Rusmawati; Haris, Asmaddy; Abdul Hamid, Kamarul Hidayah (2012)
This paper is concerned with the two main causes of skill proportion in education sector in Malaysia during the period 2002 to 2007. These are the impact of changes in within and between industrial effects. As well documented in labour economics literature, the within effects represent the changes in technological change or known as SBTC and the between effects so called the effects of trade. The paper has employed set of data comprises micro-level data from the Household Income Survey (HIS) far several years during the period 2002 ta 2007. Decomposition approach was chosen to identify the specific impact of changes in the pattern of trade and technological change on the skill proportion in education sector. Perhaps these analyses help us to look whether employment or wages factors are dominant ta lead the changes in overall labour market. We found that skill proportion in education sector in Malaysia was favour to professional workers as compared to technical and associates professionals. Technological change seemed to increase the demand for professional workers especially at tertiary sub sector. The decreasing in demand for technical and associates professional in education sector was lead by primary sub sector.